2019
DOI: 10.1186/s12889-019-6855-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of traditional risk factors of ischemic heart disease (IHD) among predominantly Malay Malaysian women

Abstract: Background The risk factors of ischemic heart disease (IHD) specific for women are less well studied. However, knowing the risk factors of IHD for women will empower women themselves to be better informed and thus can help them in decision making concerning their health condition. The objective of this study is to explore the commonly studied risk factors of ischemic heart disease (IHD) among a group of Malaysian women. Methods A case control study was conducted among 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…A study in China found that in 1990, the focus of female tobacco control was passive smoking, but in 2017, smoking and passive smoking became equally crucial for female tobacco control [ 38 ]. There is less research on risk factors for female-specific IHD, and related studies have found that passive smokers are more likely to develop IHD, so public health interventions and policy development targeting the female population are necessary [ 39 , 40 ]. We have observed that with the improvement of living conditions, modern individuals are more focused on present feelings, overlooking the various serious health consequences that smoking may bring.…”
Section: Discussionmentioning
confidence: 99%
“…A study in China found that in 1990, the focus of female tobacco control was passive smoking, but in 2017, smoking and passive smoking became equally crucial for female tobacco control [ 38 ]. There is less research on risk factors for female-specific IHD, and related studies have found that passive smokers are more likely to develop IHD, so public health interventions and policy development targeting the female population are necessary [ 39 , 40 ]. We have observed that with the improvement of living conditions, modern individuals are more focused on present feelings, overlooking the various serious health consequences that smoking may bring.…”
Section: Discussionmentioning
confidence: 99%
“…II: Non-Communicable Diseases, Risk Factors & Other Health Problems;2015," 2015 The obesity issue is associated with type II diabetes and a higher risk of developing cardiovascular disease and metabolic syndrome. (Rashid et al, 2019), (Ahmed et al, 2019) The prevalence of overweight and obesity among university student groups has risen due to the hectic lifestyle of long working hours and eating out frequently in Malaysia. (Eow et al, 2018) (Al-Naggar et al, 2013 The obesity issue among Malaysian university students will also keep increasing rapidly.…”
Section: Malaysian Obesity and Well-beingmentioning
confidence: 99%
“…In Malaysia, several studies on CHD risk factors have been conducted, however, the findings were inconclusive and contradicting between studies (12,13). Moreover, it is noteworthy that dietary factors have not been adequately examined in the previous studies.…”
Section: Introductionmentioning
confidence: 99%